Mathematical intradisciplinarity with geogebra in school mathematics - De Carvalho Faria, Rejane Waiandt Schuwartz [UNESP]; Maltempi, Marcus Vinicius [UNESP] (FapUNIFESP (SciELO), 2019)
In this paper, we discuss the intradisciplinary work in school mathematics and bring evidences that the use of GeoGebra favors it. In order to do so, we question the process of disciplining science that contributed to the deepening of various areas, at the same time as it propelled a growing dissociation among them. Similarly, the hyper-specialization of mathematical knowledge has contributed to the fragmentation of school mathematics in the arithmetic, geometry, and algebra ramifications, which has made it difficult to learn by the students. Seeking the balance between fragmentation and totalization, we investigated the intradisciplinarity of school mathematics with GeoGebra. We used a qualitative research methodology and we analyzed an activity of proportional reasoning exploration developed with mathematics teachers from an elementary school. The analysis indicate that GeoGebra allows for the exploration of multiple representations that highlight particularities of the mathematical fronts through its diverse resources and windows that present the dynamically connected mathematical objects, which contributes in a way that the disadvantages of each representation are satisfied by the advantages of the others in teaching and learning mathematics. We concluded that the intradisciplinary mathematical approach with GeoGebra emphasizes the concomitant work among the different mathematical ramifications and offers the teachers the possibility of exploring it in their pedagogical practice.
Intradisciplinaridade Matemática com GeoGebra na Matemática Escolar
Keywords: Digital technologies; Mathematical education; Proportional reasoning